Konsep Monotheisme dalam Bhagavad Gītā - Ida Bagus Subrahmaniam Saitya; I Made Ary Hardana Yasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Sad Darsana are six Indian philosophical systems that are used in the rational logic of human thought to understand the duality of the elements of the universe, the world, and humans. so that dynamic realization occurs independent dualism that stands alone in the absence of interconnection of relations